The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5937/jomb0-26008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new semi-automated Hydragel 11 von Willebrand factor multimers assay kit for routine use

Abstract: Accurate diagnosis and classification of von Willebrand disease are essential for optimal management.  The von Willebrand factor multimers analysis is in the phenotypic classification, especially in discrepant cases, an integral part of the diagnostic process. The aim of this study was to evaluate the performance of a new Hydragel 11VWF multimer assay (H11VW). Results: Comparison study did not reveal any significant difference between H5VW and H11VW.  The assessment of within-subject results, using H5VW and H1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Several independent investigators have previously reported on the analytical performance evaluation of the new Sebia technique with either 5-gel and 11-gel formats (3,12,14,15,18,20,21,23). Details of analytical performance of the Sebia method are beyond the scope of our current study.…”
Section: Calculation Of Reference Intervalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several independent investigators have previously reported on the analytical performance evaluation of the new Sebia technique with either 5-gel and 11-gel formats (3,12,14,15,18,20,21,23). Details of analytical performance of the Sebia method are beyond the scope of our current study.…”
Section: Calculation Of Reference Intervalsmentioning
confidence: 99%
“…The new semi-automated VWF multimer technique can help in standardization (26): it helps to reduce the interlaboratory variability and the variability between different measurement runs. Densitometry could contribute to its standardization by offering a reproducible quantification and additional visualization of VWF multimer patterns and permitting a precise quantitative comparison of sample patterns with those of a reference plasma curve (20).…”
Section: Calculation Of Reference Intervalsmentioning
confidence: 99%
“…Before 2016, it was not possible to confirm a suspicion of AVWS in Estonia because of a limitation of available laboratory VWF assays, while, since 2016, all VWF-related screening assays have been available to clinicians 5 and, recently, a semiautomated VWF multimer assay has been incorporated into routine clinical practice at the North Estonia Medical Centre (NEMC). 6,7 Here, we describe the clinical and laboratory data of seven patients diagnosed with AVWS at NEMC.…”
Section: Introductionmentioning
confidence: 99%
“…These assays are labour-intensive, timeconsuming, nonstandardized and may miss subtle changes. [7][8][9][10] These conventional methods have high error rates in proficiency scheme participation as reported for example by the External Quality Control of Diagnostic Assays and Tests (ECAT) scheme. 11 A new semi-automated VWF multimer electrophoresis assay, the Hydragel 5 VWF multimers kit ® (Sebia ® ), enables VWF multimer analysis and produces multimer patterns that can be visually inspected or viewed using densitometry.…”
mentioning
confidence: 99%
“…This assay is more standardized, less labour-intensive and has a shorter turnaround time when compared with conventional electrophoretic assays. [7][8][9][10] The current study aimed to verify the performance of the Hydragel 5 VWF multimers kit ® by comparing results obtained with the new assay to those obtained with existing manual electrophoretic multimer assay. 1).…”
mentioning
confidence: 99%